2006
DOI: 10.1111/j.1540-8167.2006.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of CT Image Integration into an Electroanatomic Mapping System on Clinical Outcomes of Catheter Ablation of Atrial Fibrillation

Abstract: CA for AF guided by CT integration was associated with reduced fluoroscopy times, arrhythmia recurrence, and increased restoration of sinus rhythm. Improved visualization of complex LA geometries might improve the safety and success of CA for AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
137
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(143 citation statements)
references
References 38 publications
1
137
1
4
Order By: Relevance
“…737,738 Another approach involves use of 3D rotational angiography images that can be merged with live two-dimensional fluoroscopy. 739 This approach is rarely used at the present time.…”
Section: Section 6: Technology and Toolsmentioning
confidence: 99%
“…737,738 Another approach involves use of 3D rotational angiography images that can be merged with live two-dimensional fluoroscopy. 739 This approach is rarely used at the present time.…”
Section: Section 6: Technology and Toolsmentioning
confidence: 99%
“…The surface reconstruction of the RA with superior vena cava, left atrium, PVs, RV, and LV were segmented from each chamber volume through a 3-step process as described previously. [1][2][3][4][5]7,8 Individual implanted clips within each chamber were also segmented to serve as specific, predetermined 3D CT anatomic fiducial points.…”
Section: Ct Imaging and Image Segmentationmentioning
confidence: 99%
“…Electroanatomic or impedance-based mapping systems merge preacquired, segmented computed tomographic (CT)/magnetic resonance imaging volume data sets and accompanying multidimensional maps by matching specific anatomic fiducial points seen on both anatomic and physiological renderings and simultaneously displaying them within the same coordinate system. [1][2][3][4][5][6][7][8] Although displaying an ablation catheter and integrating its position within CT/magnetic resonance geometry is possible, the accuracy of the integrated 3D geometry is highly dependent on image quality and, more importantly, on the merge process. [1][2][3][4][5][6][7][8] Errors may stem from changes in cardiac chamber volume or rhythm occurring between the time of 3D anatomic image acquisition and electroanatomic mapping in the electrophysiology laboratory.…”
mentioning
confidence: 99%
“…37 The advantage of the CartoMerge system was also reported by Kistler et al, with improved visualization of the complex LA geometry. 38 In a prospective randomized study, Della Bella et al further demonstrated the superior efficacy and long-term outcome of image-integration-guided ablation of AF over conventional fluoroscopicguided ablation. 39 Moreover, the integration also shortened fluoroscopy time, reduced the arrhythmia recurrence and increased the rate of restoration to sinus rhythm.…”
Section: Anatomical Identification and Integration Of Non-invasive Immentioning
confidence: 99%